The High Genetic Barrier of EFdA/MK-8591 Stems from Strong Interactions with the Active Site of Drug-Resistant HIV-1 Reverse Transcriptase. Issue 10 (18th October 2018) - Takamatsu, Yuki; Das, Debananda; Kohgo, Satoru; Hayashi, Hironori; Delino, Nicole S.; Sarafianos, Stefan G.; Mitsuya, Hiroaki; Maeda, Kenji
Summary: 4ʹ-Ethynyl-2-fluoro-2ʹ-deoxyadenosine (EFdA/MK-8591), a nucleoside reverse transcriptase inhibitor (NRTI) under clinical trials, is a potent and promising long-acting anti-HIV type 1 (HIV-1) agent. EFdA and its derivatives possess a modified 4ʹ-moiety and potently inhibit the replication of a wide spectrum of HIV-1 strains resistant to existing NRTIs. Here, we report that EFdA and NRTIs with a 4ʹ-ethynyl- or 4ʹ-cyano-moiety exerted activity against HIV-1 with an M184V mutation and multiple NRTI-resistant HIV-1s, whereas NRTIs with other moieties (e.g., 4ʹ-methyl) did not show this activity. Structural analysis indicated that EFdA and 4ʹ-ethynyl-NRTIs (but not other 4ʹ-modified NRTIs), formed strong van der Waals interactions with critical amino acid residues of reverse transcriptase. Such interactions were maintained even in the presence of a broad resistance-endowing M184V substitution, thus potently inhibiting drug-resistant HIV-1 strains. These findings also explain the mechanism for the potency of EFdA and provide insights for further design of anti-HIV-1 therapeutics. Graphical Abstract: Highlights: 4ʹ-Ethynyl-2-fluoro-2ʹ-deoxyadenosine (EFdA/MK-8591) is a potent anti-HIV-1 agent EFdA and its derivatives possess a modified 4ʹ-moiety 4ʹ-Ethynyl nucleoside analogs form strong interactions with reverse transcriptase These interactions are maintained even with drug-resistance-endowing mutations Abstract : EFdA exerts potent antiviral activity against multiple-drug-resistant HIV-1 strains and is now undergoing clinical trials. Takamatsu et al. evaluated the antiviral activity and structural analysis of EFdA derivatives and report that 4ʹ-ethynyl or 4ʹ-cyano moiety are the key structural features for the potent antiviral activity against drug-resistant HIV-1 strains.